(untitled) (Research, Society and Development, 2020)
Parkinson’s disease (PD) is the second most common degenerative disease of the central nervous system affecting between 1 and 2 people in 1,000 and its prevalence increases with age, affecting about 1% of the population over 60 years. Studies in the bidirectional communication between the brain and the intestine have shown that changes in the intestinal microbiota can potentially play an important role in PD and have reported gastrointestinal symptoms (constipation, dysphagia, hypersalivation and swallowing disorders). Current evidence suggests that the health and composition of the intestinal microbiome are due to the effect of diet and the use of probiotics. This study aimed to evaluate the use of probiotics and nutritional therapy for PD. The literature search was performed using the PICoS criterion to extract evidence of relevant studies from articles published in PubMed, ScienceDirect, and MEDLINE, selecting only articles with randomized clinical studies and reviews. Even with a limited number of quality studies in humans, we found research that highlighted the importance of using probiotics and diet in patients with PD, as it brings benefits to gastrointestinal motility, contributes to the symbiosis of GIT and improves stool consistency. It is concluded that the use of probiotics is a good intervention method for patients with PD. Future research should focus on the gut-brain axis and investigate how microbial populations exert pathogenic effects, as well as their interaction with diets and medications.